(3EUdGM GdCOhjI GdeSgdI hfaj eVGQgG hVQhH GSJYeGdgGs - (3MHjT Hf GdMSf GdOeTbj, GdCYSe GdOeTbj , cGf MjkG bHd (B264 (3gs ((3eMeO Hf bWH GdWHjH s)
(3ChdgG (B:s
(3CeG GdefaYI GdJi jfGdgG GHOGf GdfGS hfahSge ef TQH GdCOhjI GdeSgdI YfOeG jVWQhf Edi TQHgG s
(3BNQgG (B:s
(3agPG eG bUOfG HGUdGMg ef GdCOhjI hCeG PcQ SGFQ GdCOhjI aCfJ JYQa bhGegG hefGaYgG ef cJH GdbOeGA f CMHHJ Pdc s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B189s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(12 / 1538) s
Keywords: (3GdWHs